Social prescribing for healthy aging: sustaining social capital in India. Issue 3 (1st October 2017) - Mani, Geetha
Abstract : The proportion of the geriatric population is increasing globally, and the resultant demographic burden is becoming a significant public health concern. Apart from physical ill health associated with aging, social changes such as urbanization, migration, breakdown of the joint family system, inadequate living space, and the generation gap have a negative impact on the mental well-being of elderly people. Countries need to adopt a holistic approach. Social prescribing or community referral comprises a plethora of possible nonmedical interventions aimed at supporting people with mental health needs. Social prescribing projects in developed countries have shown significant results in terms of improved quality of life, self-confidence, social belonging, reduced physician visits, and reduced prescription of psychotropic medications. Suitable adoption of social prescribing measures in developing countries could be an effective step in converting the demographic burden of the geriatric population into a significant social capital contributing to the well-being of elderly people as well as the country.